2014
DOI: 10.1080/1045988x.2014.919138
|View full text |Cite
|
Sign up to set email alerts
|

Providing Student Opportunities to Respond in Reading and Mathematics: A Look Across Grade Levels

Abstract: The evidence for providing sufficient opportunities for students to respond has been established in terms of student engagement and achievement in reading and mathematics. Although supported by research, the question remains whether teachers are incorporating this effective practice in their classroom instruction. This study examines the analysis of data from direct teacher observations during reading and mathematics instruction. Results from the analysis indicate that there is a statistically significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Research has suggested that providing sufficient rates of OTR is effective in increasing student engagement (Carnine, 1976; Christle & Schuster, 2003; Davis & O’Neil, 2004; Haydon et al, 2010; Haydon, Mancil, & Van Loan, 2009; Sutherland, Alder, & Gunter, 2003) while decreasing disruptive behavior (Armendariz & Umbreit, 1999; Haydon et al, 2010; Haydon et al, 2009; Lambert, Cartledge, Heward, & Lo, 2006; Sutherland et al, 2003; West & Sloan, 1986). Although providing sufficient rates of OTR has been effective, in practice, teachers are demonstrating low rates of OTR across all grade levels (Whitney, Cooper, & Lingo, 2015) and are providing fewer OTR to all students when a student with EBD is in the classroom, whether it be a general education classroom or a special education classroom (Scott, Alter, & Hirn, 2011).…”
Section: Academic Engagement and Opportunities To Respond (Otr)mentioning
confidence: 99%
“…Research has suggested that providing sufficient rates of OTR is effective in increasing student engagement (Carnine, 1976; Christle & Schuster, 2003; Davis & O’Neil, 2004; Haydon et al, 2010; Haydon, Mancil, & Van Loan, 2009; Sutherland, Alder, & Gunter, 2003) while decreasing disruptive behavior (Armendariz & Umbreit, 1999; Haydon et al, 2010; Haydon et al, 2009; Lambert, Cartledge, Heward, & Lo, 2006; Sutherland et al, 2003; West & Sloan, 1986). Although providing sufficient rates of OTR has been effective, in practice, teachers are demonstrating low rates of OTR across all grade levels (Whitney, Cooper, & Lingo, 2015) and are providing fewer OTR to all students when a student with EBD is in the classroom, whether it be a general education classroom or a special education classroom (Scott, Alter, & Hirn, 2011).…”
Section: Academic Engagement and Opportunities To Respond (Otr)mentioning
confidence: 99%
“…When reviewing content, it was eight to 12 responses per minute (Council for Exceptional Children, as cited in Adamson & Lewis, 2017). Still, low rates of responding continue to occur across grade levels and content areas (Whitney et al, 2015). These low rates are especially problematic for students with high-incidence disabilities who are often academically behind, trying to play catch up, and slower to learn than their general education classmates.…”
Section: The Need For Active Student Responding In Inclusive Online I...mentioning
confidence: 99%
“…There remains a need for assessments of teacher practices that are not only useful for identifying best practices for improvement, but also useful across content areas and student age groups. Although the topics of instruction certainly differs by content area, the quantity and quality with which teachers of students at different age levels use strategies to prompt and direct behavior, or to provide academic or behavioral feedback might vary considerably (e.g., Reddy, Fabiano, Dudek, & Hsu, 2013a; Whitney, Cooper, & Lingo, 2015).…”
Section: Assessment Of Teacher Practicesmentioning
confidence: 99%